Religiousness and Minority Stress in Conservatively Religious Sexual Minorities: Lessons from Latter-day Saints. Issue 4 (2nd October 2022) - Lefevor, G. Tyler; Skidmore, Samuel J.; McGraw, James S.; Davis, Edward B.; Mansfield, Ty R.
ABSTRACT: Sexual minorities who engage in conservative religions may experience both stress and support from their engagement with their faith. However, it is unclear how religion/spirituality and minority stress may simultaneously affect mental health. To address this gap, we recruited 1, 083 U.S. adults reporting varied engagement with a conservative religious tradition, the Church of Jesus Christ of Latter-day Saints (Mormon; LDS), belonging to one of four groups: (a) heterosexual, LDS; (b) sexual minority, LDS; (c) heterosexual, nonLDS; and (d) sexual minority, nonLDS. We found that LDS sexual minorities reported more religiousness/spirituality and described experiencing more minority stressors, relative to nonLDS sexual minorities. Interaction analyses indicated that internalized homonegativity was more strongly associated with depression for LDS sexual minorities than for nonLDS sexual minorities. We suggest that aspects of religion/spirituality may buffer the effects of minority stress experienced by sexual minorities who choose to remain engaged with conservative religious traditions.